Cayratia japonica Prevents Ulcerative Colitis by Promoting M2 Macrophage Polarization through Blocking the TLR4/MAPK/NF-κB Pathway - Jun Sun; Ping Zhao; Xufeng Ding; Fang Li; Jie Jiang; Hua Huang; Lijiang Ji (Mediators of Inflammation)
Background and Aims. Several components of Cayratia japonica (CJ) such as rutin and quercetin have shown anti-inflammatory effect, yet its function in ulcerative colitis (UC) remains to be clarified. This study focuses on the modulatory effect of CJ on UC as well as molecular mechanism by which CJ regulates macrophage polarization in UC. Methods. The targets related to CJ components and UC were, respectively, obtained through in silico analysis, and their intersection targets were selected for pathway enrichment analysis. RAW264.7 cells were stimulated with lipopolysaccharide (LPS) to induce M1 macrophages. Expression of the macrophage polarization M1 marker CD11b and M2 marker CD206 was measured to determine the phenotype of macrophages. The mouse model was treated with dextran sodium sulfate (DSS) to induce UC to observe the effects of CJ on UC in vivo. Results. The in silico analysis suggested the crucial significance of TLR4 and its downstream MAPK/NF-κB pathways in the modulatory effect of CJ on UC. Furthermore, experimental data revealed that CJ could promote M2 macrophage polarization but alleviate immune inflammation and reduce colon damage in DSS-evoked UC model. Additionally, CJ can inhibit the expression of TLR4/MAPK/NF-κB signaling pathway to enhance the M2-like polarization. Conclusion. Hence, CJ may exert anti-inflammatory effects and an inhibitory role in UC by inhibiting the TLR4/MAPK/NF-κB pathway and subsequent M1-like macrophage polarization.